Amblyomma triste (Koch, 1844) (Acari : Ixodidae) Ovaries: An ultrastructural analysis - de Oliveira, Patricia Rosa; Bechara, Gervasio Henrique; Camargo Mathias, Maria Izabel (Elsevier B.V., 2007)
This study presents an ultrastructural analysis of the ovary of the tick, Amblyomma triste. The ovary of this species is of the panoistic type that is, without nursing and follicular cells. It is composed of a layer of epithelial cells forming a wall and of germinative cells that generate the oocytes which remain attached to the external margin of this wall by a multicellular pedicel. The different developmental stages in the oocytes had been described by Oliveira et al. [Oliveira, P.R., Bechara, G.H., Camargo-Mathias, M.I., 2006. Amblyomma triste (Koch, 1844) (Acari: Ixodidae): Morphological description of the ovary and of vitellogenesis. Experimental Parasitology 113, 179-185]. The results of the investigation suggest that besides exogenous production of vitellogenic elements, endogenous production can take place simultaneously, contributing to the development and growth of the oocytes. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Anblyomma triste; tick; ovary; vitellogenesis; ultrastructure